The embodied playbook: writing practices of student-athletes - Rifenburg, J. Michael, author; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Understanding student literacy in a surprising place: the university athletic department. Through analysis of a year-long case study of a university men's basketball team, showing a deeper and refined understanding of how humans learn through the body can help writing instructors reach a greater range of students..--Provided by publisher.
Knowing our student-athletes -- What are plays and what do they do?: a textual analysis of scripted plays -- How do student-athletes learn plays?: a narrative of a Division II men's basketball team -- How can we better teach our student-athlete writers?: a narrative of a Division I writing center -- How can we better teach our student-athlete writers?: writing practices as jazzy, creative, collaborative.
Keywords: College athletes -- Education -- United States; English language -- Rhetoric -- Study and teaching (Higher) -- United States; Learning strategies